DNA methylation and demethylation in adipocyte biology: roles of DNMT and TET proteins in metabolic disorders - Wu, Lijiao; Wang, Xiangjin; Wang, Luling; Li, Shuyan; Chen, Qiu (Frontiers in Endocrinology, 2025)
Adipocytes play a crucial role in regulating energy metabolism throughout the body. Dysfunctional adipocyte biology is a primary factor in the development of metabolic disorders associated with obesity and type 2 diabetes. Over the past decades, the role of epigenetic mechanisms, particularly DNA methylation, in the development and regulation of adipocytes has been extensively elucidated. These mechanisms influence numerous biological processes in adipose tissue and adipocytes, including lipogenesis and lipid metabolism. With the discovery of the active DNA demethylation mechanism centered on ten-eleven translocation (TET) proteins, a growing body of evidence sug-gests that DNA demethylation mechanisms also profoundly influence various aspects of adipocyte biology and regulate cellular differentiation and function by altering the methylation status of genes. Following the discovery of active DNA demethylation mechanisms mediated by TET proteins, a growing body of evidence indicates that these mechanisms profoundly influence multiple aspects of adipocyte biology. Specifically, these mechanisms regulate cellular differentiation and function by altering the methylation status of key genes involved in adipogenesis and metabolism. A precise and detailed understanding of the mechanisms underlying DNA demethylation in adipocyte biology is imperative for the identification of novel interventional therapies targeting adipocyte gene methylation and demethylation. This review examines the specific molecular mechanisms and significance of passive and active DNA demethylation in adipocyte biology, focusing on the DNA methyltransferase family and TET proteins. It summarizes crosstalk mechanisms involving DNA methyltransferases, highlights the multiple action pathways of TET proteins, and reveals the potential of additional intervention pathways. This review aims to provide an updated theoretical basis for promising therapeutic targets.